Fluorescence In Situ Hybridization in Primary Diagnosis of Biliary Strictures: A Single-Center Prospective Interventional Study - Vincent Dansou Zoundjiekpon; Premysl Falt; Jana Zapletalova; Petr Vanek; Daniela Kurfurstova; Zuzana Slobodova; Daniela Skanderova; Gabriela Korinkova; Pavel Skalicky; Martin Lovecek; Ondrej Urban (Biomedicines, 2023)
Background and aims: Diagnosis of the biliary stricture remains a challenge. In view of the low sensitivity of brush cytology (BC), fluorescence in situ hybridization (FISH) has been reported as a useful adjunctive test in patients with biliary strictures. We aimed to determine performance characteristics of BC and FISH individually and in combination (BC + FISH) in the primary diagnosis of biliary strictures. Methods: This single-center prospective study was conducted between April 2019 and January 2021. Consecutive patients with unsampled biliary strictures undergoing first endoscopic retrograde cholangiopancreatography in our institution were included. Tissue specimens from two standardized transpapillary brushings from the strictures were examined by routine cytology and FISH. Histopathological confirmation after surgery or 12-month follow-up was regarded as the reference standard for final diagnosis. Results: Of 109 enrolled patients, six were excluded and one lost from the final analysis. In the remaining 102 patients (60.8% males, mean age 67.4, range 25–92 years), the proportions of benign and malignant strictures were 28 (27.5%) and 74 (72.5%), respectively. The proportions of proximal and distal strictures were 26 (25.5%) and 76 (74.5%), respectively. In comparison to BC alone, FISH increased the sensitivity from 36.1% to 50.7% (p = 0.076) while maintaining similar specificity (p = 0.311). Conclusions: Dual-modality tissue evaluation using BC + FISH showed an improving trend in sensitivity for the primary diagnosis of biliary strictures when compared with BC alone.